The Integrating Emotional Intelligence and Resilience: Approaches for Enhancing Well-Being and Coping in Diverse Workplaces - Razia Yasmeen; Zeeshan Munawar; Mirza, Farhat Abbass (International Journal on Integrated Education, 2023)
Diversity and inclusion are crucial to corporate success in the worldwide workplace. However, more diversity may lead to interpersonal problems, misunderstanding, and workplace stress, which can lead to job burnout and worse employee well-being. This research examines how emotional intelligence (EI) and resilience might help people overcome these problems. According to Social Cognitive Theory, resilient people can better comprehend, react to, and learn from workplace social signals and stresses. We also examine how executive capabilities including working memory, cognitive flexibility, and inhibitory control affect EL and resilience strategies. Through a thorough assessment of hedonic and eudaimonic well-being studies, we emphasize the relevance of developing both to improve employee life satisfaction and performance. This research also discusses how EI and resilience may be used to negotiate social influence phenomena like compliance and conformity to foster good social connections and lessen peer pressure. To address methodological problems, we explore possible biases in this study and suggest ways to mitigate them. We also use mediation analysis to investigate the intricate linkages between EI, resilience, workplace diversity, and employee well-being. We acknowledge missing data in social science research and provide practical advice on how to manage it for strong and credible research outcomes. This study seeks to explain how El and resilience may be used to create a happy, inclusive, and successful workplace by linking psychological research disciplines.